Factors affecting Credit Risk with the Impact of Covid-19: A Study on Islamic Banks in Malaysia - Jaafar, Mohamad Nizam; Saddam, Siti Zaitun; Muhamat, Amirul Afif; Zuhairi, Farha SyamilaMohd; Abd Aziz, Nurul Amiera (Journal of Entrepreneurship, Business and Economics; Vol 11 No 1 (2023), 2023)
Banks and financial institutions around the world manage the investments of countless consumers. Only a handful of consumers have excellent credit, particularly during the current pandemic of COVID-19. Hence, in the field of credit risk management, the assessment of reflecting and calibrating credit risk is very important and must be carried out accurately. It must be properly administered to survive in the banking industry’s ever-increasing competitiveness. Thus, this paper examines factors affecting credit risk in Islamic banking in Malaysia. Moreover, pinpoints the relationship between COVID-19 and Islamic banking credit risk as it imposes a threat to the profitability of banks. Data from the Annual report of 16 Islamic banks were collected for nine years from 2013 to 2021, and panel data analysis was used in this study. The results show that profitability (PR), bank inefficiency (EFF), and bank capitalization (CAP) affect Islamic banks’ credit, and bank inefficiency (EFF) was selected as the most important variable affecting Islamic banking credit risk during the COVID-19 pandemic. In general, this study proved that Islamic banks in Malaysia can survive COVID-19 and have good risk management to reduce losses. Research paper Keywords: Credit Risk, COVID-19, Panel Data, Islamic Bank, Fixed Effect Reference to this paper should be made as follows: Jaafar, M. N., Saddam, S. Z., Muhamat, A. A., Mohd Zuhairi, F. S., & Abd Aziz, N. A. (2023). Factors affecting Credit Risk with the Impact of Covid-19: A Study on Islamic Banks in Malaysia. Journal of Entrepreneurship, Business and Economics , 11 (1), 153–179.